Hepatocellular Carcinoma Targeting and Pharmacodynamics of Paclitaxel Nanoliposomes Modified by Glycyrrhetinic Acid and Ferric Tetroxide - Zhao, Ling; Liang, Leyi; Guo, Mimi; Li, Ming; Yu, Xuesong; Wang, Ying; Wang, Yan (Current Topics in Medicinal Chemistry, 2021)
Aims: Research on developing targeted delivery of anticancer drugs for the treatment of hepatocellular carcinoma (HCC) is ongoing. This study aimed to synthesize nanoliposomes modified by glycyrrhetinic acid (GA) and ferric tetroxide (Fe3O4) for targeted delivery of paclitaxel for selective and specific therapy of HCC. Objective: During this project, GA and Fe3O4 were used to jointly modify the active targeting and magnetic orientation of paclitaxel nanoliposomes for enhanced targeting of HCC to improve the efficacy, while reducing the systemic toxicity and side effects of the drug. Methods: In this study, liposomes were prepared utilizing a thin film dispersion method, in which the average particle size of GA/Fe3O4-PTX-LP was 148.9 ± 2.3 nm, and the average Zeta potential was -23.2 ± 3 mV. Based on TEM characterization, GA/Fe3O4-PTX-LP is a closed particle with bilayer membranes. In vitro release assessments of the drug indicated that the release of GA/Fe3O4- PTX-LP was sustained. Results: In vitro cell tests have demonstrated that GA/Fe3O 4-PTX-LP can inhibit the proliferation, affect the morphology, migration and invasion, and interfere with the cycle of HCC cells. Uptake tests have confirmed that GA/Fe3O4-PTX-LP can promote the uptake of the drug in HCC cells. Conclusion: In vivo targeting experiments have shown that GA/Fe3O4-PTX-LP has a strong ability to target tumors. In vivo antitumor assessments have proven that GA/Fe3O4-PTX-LP can inhibit tumor growth without obvious toxicity. This project provides a promising nano-targeted drug delivery system for the treatment of HCC.
Keywords: Tumor targeting